The immunogenic potential of AZD1402 (Elarekibep) T-cell epitopes in healthy volunteers and drug-exposed clinical trial participants - Liam Farrell; Stephanie M Bates; Alexander Walker; Monday Ogese; Xiaoli Meng; Sian Piper; John Mo; Katy Saide; Jorrit Hornberg; David Close; Ian Wallace; Catherine J Betts; et al. (Archives of Toxicology, 2026)
AZD1402 (Elarekibep) is a novel anticalin with engineered IL-4Rα antagonist binding properties that was under development for inhaled treatment of asthma. Structural similarity to tear-lipocalin is thought to limit immunogenicity risk; however, a range of treatment-emergent hypersensitivity-like adverse events were observed in a clinical study. This study aimed to (i) explore the activation of drug-exposed human T-cells with AZD1402- and tear lipocalin-derived peptides, (ii) characterise any T-cell epitopes contained within AZD1402 and (iii) define the nature of any response. Peripheral blood mononuclear cells (PBMC) from AZD1402-exposed study participants, alongside AZD1402-naïve donors, were cultured with AZD1402 and AZD1402-derived overlapping 18mer peptides. Proliferation and cytokine secretion were measured. T-cell clones were generated to characterise the diversity of T-cell epitopes and reactivity against equivalent tear-lipocalin peptides. AZD1402 contained multiple epitopes located in engineered “hotspot” regions of the molecule that activated PBMC and MHC class II-restricted CD4 + T-cell clones from both study participants and AZD1402-naïve donors. T-cell stimulatory peptides contained amino acid substitutions generated through mutagenesis to create AZD1402 target binding properties; similar T-cell epitopes were not found in tear-lipocalin. Detection of T-cell clones responsive towards AZD1402 and AZD1402-derived peptides provides evidence that immunogenic epitopes are formed naturally through processing of the AZD1402. These data describe a recall immunogenicity risk associated with AZD1402 and provide a framework by which to explore the immunogenic potential of modified sequences within anticalin or other large molecule therapeutics.